2020
DOI: 10.1016/j.heliyon.2020.e04449
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer activities of Vernonia amygdalina Delile. Leaves on 4T1 breast cancer cells through phosphoinositide 3-kinase (PI3K) pathway

Abstract: Vernonia amygdalina Delile ( Asteraceae ) is used in traditional medicine to treat diabetes mellitus, and some research provides its activity to treat breast cancer. The aim of this study is to assess the anticancer activity of Vernonia amygdalina Delile leaves fractions on 4T1 breast cancer cells. Analysis of phytochemical compounds were carried out with LC-MS/MS. Cytotoxic activity was determined using the MTT method in the 4T1 cell line. Apoptosis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Some of them are new compounds and this will be very useful for drug development [25]. Secondary metabolites, when taken as a single component or in combination, can be effective and safe even when synthetic medications fail [26]. They may potentially enhance or synergize the effects of other pharmaceutical ingredients [27] for further discussion will be discussed the relationship of secondary metabolites and their pharmacological activity in L. domesticum Corr.…”
Section: Natural Product Identification Of L Domesticum Corrmentioning
confidence: 99%
“…Some of them are new compounds and this will be very useful for drug development [25]. Secondary metabolites, when taken as a single component or in combination, can be effective and safe even when synthetic medications fail [26]. They may potentially enhance or synergize the effects of other pharmaceutical ingredients [27] for further discussion will be discussed the relationship of secondary metabolites and their pharmacological activity in L. domesticum Corr.…”
Section: Natural Product Identification Of L Domesticum Corrmentioning
confidence: 99%
“…An antidiabetic effect of VA was reported by Erukainure et al [ 13 ], while Okunlola et al [ 14 ] gave a report of its antioxidant properties. Additionally, its anticancer property has been reported [ 15 ]. Some bioactive constituents have been identified in the leaves of the plant, including steroid glycosides like vernonioside A1, A2, A3 [ 16 ] and vernonioside B2, B3, B4 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of polyphenols, vitamins and mineral salts make the plant useful in human diets [25,26]. V. amygdalina is very rich in phytochemicals such as saponins, sesquiterpenes, flavonoids, and steroid glycosides (vernosides), lactones [26] and several studies reported that it has anticancer and antitumor activity [27,28]; antihepatotoxic activity [29]; hypoglycemic activity [26]; antibacterial activity [30]; anti-inflammatory [31] as well as antioxidant property [32].…”
mentioning
confidence: 99%